Will Millennials Invest In Retail Sukuk? The Case Of Malaysia And Indonesia - Sulistya Rusgianto; Nanda Lismatiara Zubaid; Nursilah Ahmad (Fakulti Ekonomi dan Muamalat, Universiti Sains Islam Malaysia, 2024)
Sukuk issuances play a critical role in promoting economic growth. At present, there are moves towards introducing sukuk at the retail level online to make it accessible to the public. This is a way for the government to raise financing domestically. The present study investigates the knowledge and preferences of millennials towards retail sukuk offered in Malaysia and Indonesia. For that purpose, survey questionnaires are distributed in early 2022 to 135 respondents to examine their perceptions and awareness of sukuk investment using purposive samplings. Identifying factors influencing millennials investing in retail sukuk will contribute to the development of Islamic financial products and services in Malaysia and Indonesia. The findings suggest that values and technology-fit tasks are important variables in sukuk investment among the respondents. Millennial investors have an important role in developing sukuk investment products and services. To the policymakers, the findings will provide an early profile of investors millennials who are more inclined to use technological advances in investing. It is important to understand millennials' values, behavior, and preferences to appropriately assess both opportunities and risks in investing.